B2 Cell-based assays of CAG repeat instability in the huntingtin (HTT) gene. (13th September 2016) - Massey, Tom; Elliston, Linda; Donaldson, Jasmine; Smith, Laura; Allen, Nicholas; Jones, Lesley
Abstract : Background: The CAG repeat expansion in the HTT gene that causes Huntington's disease (HD) is known to vary in length, both intergenerationally and between different tissues within one patient. Repeat expansion in the striatum correlates with the neurodegeneration seen in HD, and one explanation is that repeat expansion drives pathogenesis. Recent work on genetic modifiers has identified DNA repair pathways as influences on the age at onset of HD, and they may act through CAG repeat length changes. Aims: To develop a cell-based system in which genetic and environmental influences on CAG repeat instability can be tested. Methods: An immortalised murine striatal cell line (STHdh (Q111/+)) and a number of human induced pluripotent stem cell lines (with different numbers of CAG repeats- 33, 60, or 109) were cultured under a wide range of conditions and CAG repeat stability measured. Conditions tested at various timepoints included oxidative stress (hydrogen peroxide), DNA damage (mitomycin C, methyl methanesulfonate, UV irradiation), cell cycle arrest (restrictive temperature, hydroxyurea), and cellular differentiation. Following cell growth and treatment genomic DNA was extracted, FAM-labelled PCR across the CAG repeat performed, and repeat length assessed by capillary electrophoresis (AB3130xl capillary sequencer using a 500 LIZ size standard). Results: Modest but reproducible expansion of the CAG repeat (1–2 repeats per passage) was observed in the iPSC line containing 109 repeats STHdh under non-differentiated conditions. The murine cells had a stable CAG repeat in all conditions tested. Conclusions: CAG repeat expansion can be observed in human iPSC lines with longer repeat lengths but not in the STHdh (Q111/+) immortalised murine line. The modest background CAG instability of the human iPSC line makes it a good model for further work to test genetic and environmental modifiers of CAG repeat length.